Transforming Rural Farm Livelihoods : The NRLM Journey - Singh, Anjani Kumar; Pinto, Alreena Renita; Singh, Paramveer; De, Alok (World Bank, Washington, DC, 2020)
The agriculture sector is the largest employer in India, providing direct employment to more than fifty percent of the nation’s workforce. Small and marginal farmers with landholdings of less than two hectares comprise eighty-six percent of all agricultural labour, reflecting high land fragmentation and low economies of scale. Mainstream extension and agriculture support services are not customized for these farmer segments, limiting their capacity to access improved production inputs and technology. The situation is even more complicated for women farmers who constitute nearly forty-three percent of India’s agricultural labour force. The DAY-NRLM farm livelihoods strategy evolved against this background to leverage the program’s social infrastructure of sixty-eight million households mobilized into exclusively women based self healp groups (SHGs) and higher federations, in order to deliver intensive and targeted capacity building of small farmers and streamline access to credit for farm needs. Key sub-sectors under the DAY-NRLM farm livelihoods portfolio include agriculture, livestock and non-timber Forest Produce (NTFP), supported through a combination of programs including the Mahila kisan sashaktikaran pariyojna (MKSP), National rural livelihoods project (NRLP) and Sustainable livelihoods and adaptation to climate change (SLACC). The farm livelihoods strategy under DAY-NRLM has evolved over the years from its initial focus on enhancing productivity through improved inputs and production methods, to a suite of interventions that address multiple entry points in the agriculture value chain.